Genome-wide analysis of the MADS-Box gene family in Chrysanthemum. (February 2021) - Won, So Youn; Jung, Jae-A; Kim, Jung Sun
Graphical abstract: Highlights: 108 putative MADS-box transcription factor genes were identified in chrysanthemum. Each gene class has specific conserved protein motifs and exon–intron structures. The genes are differentially expressed in different tissues based on RNA-seq data. Abstract: MADS-box family transcription factors play key roles in various developmental processes in plants. Here, we identified 108 MADS-box genes in the genome of chrysanthemum ( Chrysanthemum nankingense ). We classified these genes based on their phylogenetic relationships with MADS-box genes in Arabidopsis thaliana and lettuce ( Lactuca sativa ). Type I genes were subdivided into classes Mα (19 genes), Mβ (12 genes), and Mγ (10 genes), and type II genes were subdivided into classes MIKC C (64 genes) and MIKC* (3 genes). The MIKC C class genes were further divided into 16 subclasses that included genes described in the ABCDE flower development model. Each group of MADS-box genes showed a specific pattern of conserved protein motifs and exon–intron structure. We analyzed the expression levels of each MADS-box gene in root, stem, leaf, flower bud, disc floret, and ray floret tissues. Subfamilies AGL18, FLC, and SVP contained more members in chrysanthemum. The asterid-specific TM8 subfamily and eleven Asteraceae Specific-MADS CnMADS genes were present in chrysanthemum. Chrysanthemum is the lacking members of the AGL15 subfamily. Among the genes responsible for the ABCDE model, B-class genes were expanded in chrysanthemum with three AP3 and four PI genes. One AP3 homolog functions in marginal ray floret development, whereas the two other AP3 homologs function in the development of the central disc floret. Two of the four PI genes are expressed in chrysanthemum, specifically in both types of florets. The results of this study lay the foundation for further studies of the roles of MADS-box genes in flower development in chrysanthemum and of the evolution of MADS-box genes in plants.